- #1

- 142

- 0

Consider case (c), (case (c) involved two waves with equal wavelength and amplitude, but with some arbitrary phase difference), and write the two waves as

[tex]y1(x) = Acos((\frac{2*\pi*x}{\lambda}))[/tex]

[tex]y2(x) = Acos((\frac{2*\pi*x}{\lambda}) + \phi) [/tex]

where [tex]\lambda[/tex] and [tex]A[/tex] are the common wavelength and amplitude of the two waves and [tex]\phi[/tex] is their phase difference. Calculate the sum wave [tex]y(x) = y1(x) + y2(x)[/tex] and find an expression for the amplitude of the sum wave in terms of [tex]A[/tex] and [tex]\phi[/tex].

Find an expression for Amplitude in terms of the amplitude?? What exactly is this question asking?